HbMYB44, a Rubber Tree MYB Transcription Factor With Versatile Functions in Modulating Multiple Phytohormone Signaling and Abiotic Stress Responses - Qin, Bi; Fan, Song-Le; Yu, Hai-Yang; Lu, Yan-Xi; Wang, Li-Feng (Frontiers in Plant Science, 2022)
The vital roles of R2R3-MYB transcription factors (TFs) in regulating stress response and phytohormone signaling have been thoroughly studied in numerous plants species, but the functions of these TFs in rubber tree are poorly understood. Rubber tree is the most important source of natural rubber but often suffers from various abiotic and biotic stresses that cause severe yield losses each year. Here, we reported a novel MYB44 gene in rubber tree (named HbMYB44) and revealed its biological function. HbMYB44 was highly similar to AtMYB44 and clustered into subgroup 22. Transient expression indicated that HbMYB44 is a nuclear localized protein and displays transactivation activity at the C-terminus. HbMYB44 was ubiquitously expressed in rubber tree, and its expression was strongly induced by multiple phytohormones, drought stress, wounding, and H2O2 treatments. Furthermore, overexpression of HbMYB44 in Arabidopsis (OE) demonstrated that OE plants significantly enhanced stress tolerance, i.e., salt stress, osmotic stress, and drought stress. Additionally, HbMYB44 promoted recovery from root growth inhibition of OE plants caused by exogenous phytohormones (including ABA, MeJA, GA3, and SA), but the opposite effect was present in response to ET. Interestingly, HbMYB44 increased the expression of its homologous genes and interacting protein-encoding genes in OE plants. Overall, HbMYB44 plays versatile functions in modulating multiple phytohormone signaling pathways and in stress tolerance.